An exploration of clinical psychology's response to parental bereavement in adults with intellectual disability. Issue 6 (3rd July 2017) - Irwin, Lynn; O'Malley, Grace; Neelofur, Shazia; Guerin, Suzanne
Abstract : Background: The dearth of literature regarding how or when to intervene when an adult with intellectual disability is bereaved may impede clinical practice; this study therefore aimed to explore the current clinical psychology response, so as to enhance understanding of the role of the profession in supporting grief within this population. Method: A collective case study design was used. Data for six persons with intellectual disability, including interviews with parentally bereaved persons and involved staff members, were integrated into individual case stories for cross‐case synthesis. Results: Data were analysed using thematic analysis. Five overarching themes illustrated that the clinical psychology role is broadly distributed and identified potentially complicating factors such as "gatekeeping" and "staff uncertainty." Conclusions: A model of bereavement supports reflecting that by Read ( Learning Disability Practice, 8, 2005, 31) is being approximated in clinical practice; further research is required to determine how best to implement this, and whether this meets the true needs of the population.